EDUCATING THE HEART OF A PILGRIM: IN CONVERSATIONS WITH DILEXIT NOS AND SPES NON CONFUNDIT - Firmansyah, Antonius (Sanata Dharma University, 2024)
Christians are pilgrims on this earth journeying towards the fulfilment of time. At the same time, they are also journeying along so many different axes of this world. Harmonizing the two journeys presents the Christians with a never-ending task of spiritually revitalizing themselves. The excess of progressing through secular journey as Christians brings a lot of toils to the center of their spirituality, the heart. Pope Francis's recent encyclic, Dilexit Nos, provides us with insights into the spiritual capacity of the heart. Especially, his treatment of St. Ignatius of Loyola’s Spiritual Exercises on the human heart may provide us with inspiration on the heart as the source of spiritual energy for journeying on the pilgrimage in this world. Applying different literatures of theology of spirituality to read the Encyclic, this paper will elaborate the role of the Exercises in nurturing our heart as the locus of spiritual pilgrimage. In combination with Pope Francis’ bull for the Jubilee of 2025, Spes Non Confundit, we can conclude that the sign of heart ready for a spiritual pilgrimage lies in its ability to grow eschatological hope. The spiritual pilgrimage of Christians needs to be based on the capacity of the heart to hope in the process towards the fulfillment of God’s Kingdom.